Exploration of Instant Functional Drinks Based on Angkak and Kidney Bean Flour: Implications on Bioactive Compound and Antioxidant Activity - Sari, Rinten Anjang; Utami, Riana Pangestu; Natalie, Umboh Ruth Gloria (Journal of Agri-Food Science and Technology, 2025)
Indonesian eating patterns have shifted to more fast food, which is high in fat and free radicals. Free radicals are unstable and highly reactive molecules and will react with surrounding molecules to obtain electron pairs. Angkak and kidney bean flour contain bioactive compounds such as alkaloids, phenols, terpenoids, triterpenoids, flavonoids, isoflavonoids, flobatananis, coumarins, and saponins that could act as antioxidants. Both food ingredients can be modified into functional instant drinks to increase their benefits in providing daily antioxidant intake. Instant powder drinks are one of the alternative ways to get the benefits of plants or food. They have a pharmacological effect health, as they are used or consumed more easily and practically. This study aimed to contribute to producing an instant functional drink high in bioactive compounds and antioxidants as an alternative functional food. The research design used was a single-factor Complete Randomized Design (CRD) with four treatments, each repeated 3 times, so that 12 experimental units were obtained. The treatment in the study of making instant powder drinks consisting of the ratio of angkak and kidney bean flour was P1 (50:50%), P2 (40:60%), P3 (30:70%), and P4 (20:80%). Phenol, flavonoid, and antioxidant activity values were highest successively in the F4 treatment of 31.895 mg/L, 47.800 mg/L, and 60.996 μg/ml. The results show that instant powder drinks of kidney bean flour and angkak are included in the strong category and can be used as functional drinks high in antioxidants.